FORMING CREATIVE THINKING THROUGH PROBLEMS AND EXERCISES FROM MOLECULAR BIOLOGY IN PROVIDING PERSONAL DEVELOPMENT IN THE EDUCATIONAL SYSTEM (American Journal of Interdisciplinary Research and Development, 2023)
This article deals with the issue of teaching the basics of molecular biology within the subject of biology to general secondary school students in the educational system, ensuring the personal development of pupils and students in teaching molecular biology in higher education institutions, and the role and importance of using exercises in the development of creative thinking, andmethodologyexplained.